Iowa RBA, December 6-12, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Emails of Iowa RBA updates for December 6-11, 1999. Highlights of the updates include sightings of a Yellow-billed Loon, Prairie Falcon, Varied Thrush, Lesser Black-backed Gull, and White-winged Crossbills. Includes seven Iowa RBA update emails and an email from Francis L. Moore regarding the Yellow-billed Loon. Epson - sheet feed/flatbed